A Conceptual Model for the Development of a National Cybersecurity Index: An Integrated Framework - Koong, Kai (2015)
As ICT and cyberspace become sources of impressive innovation, the reliance of organizations, governments, and people on them will increase. However, with this vast reliance, hazardous vulnerabilities have emerged. These vulnerabilities may be exploited, resulting in information and cybersecurity issues at the national as well as the international levels. Cybersecurity is critical for sustaining resilience in critical infrastructures (CI) as well as information infrastructures (CII). Accordingly, cybersecurity should be incorporated into the economic and national security model of a nation. With this in mind, a cybersecurity index is a necessary tool to compare the performance of nations in terms of cybersecurity initiatives, and in articulating effective cybersecurity policies and strategies. This paper proposes a holistic framework for building a cybersecurity index taking into consideration the technological, legal, economic, cultural, and international relations factors pertinent to countries and paves the way for cybersecurity measures and metrics to be established and tested.